Perceptions of Small-scale Fishermen on the Impact of Climate Change in Coastal and Small Island Areas of Pangkajene and Islands Regency - Kasri, Kasri; Hasani, M. Chasyim; Baso, Aris; Amiluddin, Amiluddin (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2024)
This study examines the perceptions of small-scale fishers in coastal areas and small islands of Pangkep Regency towards the impacts of climate change. The impacts of climate change experienced by fishers include unpredictable changes in weather patterns, increased sea temperatures, and unpredictable fishing seasons, which overall reduce catches and increase safety risks at sea. The research was conducted for 6 months from May to October 2024. The research was conducted in Pangkep District, South Sulawesi. The research location was purposively selected to illustrate the condition of fishermen who are directly affected by climate change. Data collection techniques were conducted through in-depth interviews, direct observation, questionnaires, and literature studies. The number of samples in this study were 50 fishermen with the criteria of small fishermen who have a ship/boat capacity of 0-10 GT. This research used a qualitative approach with a descriptive method. The qualitative approach allows researchers to explore fishermen's subjective perceptions of the impacts of climate change. Most fishers reported a decrease in catches due to changes in fish migration thought to be related to rising seawater temperatures, which forced them to go further out to sea and incur greater operational costs. In addition, climate change is resulting in extreme weather that often poses accident risks for fishers, while limited access to weather information and technology hinders their adaptation. This suggests the need for adaptation policies, such as climate training and improved access to weather information for small-scale fishers, to strengthen their resilience to climate change.